Gut microbiota-derived butyrate regulates gut mucus barrier repair by activating the macrophage/WNT/ERK signaling pathway. Issue 4 (25th February 2022) - Liang, Liping; Liu, Le; Zhou, Wanyan; Yang, Chenghai; Mai, Genghui; Li, Haolin; Chen, Ye
Abstract: Ulcerative colitis (UC) is majorly associated with dysregulation of the dynamic cross-talk among microbial metabolites, intestinal epithelial cells, and macrophages. Several studies have reported the significant role of butyrate in host–microbiota communication. However, whether butyrate provides anti-inflammatory profiles in macrophages, thus contributing to UC intestinal mucus barrier protection, has currently remained elusive. In the current study, we found that butyrate increased mucin production and the proportion of mucin-secreting goblet cells in the colon crypt in a macrophage-dependent manner by using clodronate liposomes. Furthermore, in vivo and in vitro studies were conducted, validating that butyrate facilitates M2 macrophage polarization with the elevated expressions of CD206 and arginase-1 (Arg1). In macrophages/goblet-like LS174T cells co-culture systems, butyrate-primed M2 macrophages significantly enhanced the expression of mucin-2 ( MUC2 ) and SPDEF (goblet cell marker genes) than butyrate alone, while blockade of WNTs secretion or ERK1/2 activation significantly decreased the beneficial effect of butyrate-primed macrophages on goblet cell function. Additionally, the adoptive transfer of butyrate-induced M2 macrophages facilitated the generation of goblet cells and mucus restoration following dextran sulfate sodium (DSS) insult. Taken together, our results revealed a novel mediator of macrophage–goblet cell cross-talk associated with the regulation of epithelial barrier integrity, implying that the microbial metabolite butyrate may serve as a candidate therapeutic target for UC.